Improving The Methodology For Developing Students’ Professional Competence Based On Digital Educational Technologies In Higher Education (Journal of Pedagogical Inventions and Practices, 2026)
This article explores the methodological improvement of developing students’ professional competence based on digital educational technologies in higher education institutions. The study analyzes the role of digital transformation in reshaping pedagogical processes, learning environments, and competency formation strategies. Particular attention is given to the integration of digital learning tools, artificial intelligence systems, blended learning models, and competency-based educational approaches. The research highlights that the effectiveness of professional competence development depends on the systematic implementation of innovative pedagogical conditions, the digital readiness of teaching staff, and the active involvement of students in self-directed learning processes. The findings demonstrate that digital educational technologies significantly enhance personalization, interactivity, and efficiency of the learning process, thereby ensuring alignment with modern labor market requirements